Aeromonas spp. IN FARMED FISH IN BRAZIL: A SYSTEMATIC LITERATURE REVIEW (REMUNOM, 2025)
The genus Aeromonas comprises more than 30 species of bacteria widely distributed in aquatic environments and frequently associated with opportunistic infections in aquatic organisms, especially farmed fish. In aquaculture systems, these bacteria can cause septicemia, high mortality rates, and economic losses, and pose a potential risk to public health. Therefore, this study aimed to conduct a systematic review of the scientific literature on the occurrence of Aeromonas spp. in farmed fish in Brazil, from 2012 to 2022. Searches were conducted in the ScienceDirect, CAPES Journals, SciELO, and PubMed databases, using the English descriptors "Aeromonas," "aquaculture," "diseases," "fish," and "Brazil," combined with the Boolean operator "AND," according to the specificities of each database. Of the 151 studies identified, 10 articles met the established criteria and were included in the final analysis. The species Aeromonas bestiarum, A. caviae, A. dhakensis, A. jandaei, A. hydrophila, and A. veronii were identified in five species of farmed fish: tambaqui, jundiá, pacu, tilapia, and hybrid surubim, in the states of Amazonas, Mato Grosso do Sul, Pernambuco, Paraná, Rio Grande do Sul, and São Paulo. The isolates presented varied virulence profiles and resistance to different antibiotics. All Aeromonas species were isolated from tambaqui, 80% from tilapia, 60% from pacu, and 20% from jundiá and hybrid surubim. Additionally, isolates of the genus Aeromonas without species identification were reported in tambaqui and jundiá. The results highlight the scarcity of studies on Aeromonas spp. in farmed fish in Brazil, indicating a relevant scientific gap, especially considering the growth of national fish farming and the emergence of this bacterial genus as a pathogen of sanitary importance.